Covenant of care : Newark Beth Israel and the Jewish Hospital in America - Kraut, Alan M. (Rutgers University Press, 2007)
Where were you born? Were you born at the Beth? Many thousands of Americans--Jewish and non-Jewish--were born at a hospital bearing the Star of David and named Beth Israel, Mount Sinai, or Montefiore. Newark Beth Israel Hospital is a distinguished modern medical institution in New Jersey whose history opens a window on American health care, the immigrant experience, the religious impulse for health care, and urban life. Alan and Deborah Kraut tell the story of this important institution, illuminating the broader history of voluntary nonprofit hospitals created under religious auspices initially.